Limiting Added Sugars and Fats - Jennifer Hillan; Claudia Peñuela (EDIS)
Revised! FCS8719, a 1-page handout by Jennifer Hillan and Claudia Peñuela, provides a crossword puzzle to practice knowledge of some healthy substitutions for fats, oils, and sweets. Published by the UF Department of Family, Youth and Community Sciences, October 2010.